Creating shared value through sustainable partnerships: The role of CSR in the spice farming sector in Indonesia - Mulyani, Sekar Inten; Karsidi, Ravik; Kartono, Drajat Tri; Anantanyu, Sapja (Research Journal in Advanced Humanities, 2025)
The primary objective of this study is to examine the operationalization of Creating Shared Value (CSV) within a Corporate Social Responsibility (CSR) partnership initiative among corporations primarily engaged in the agricultural sector, collaborating with spice farmers. A case study was employed to explore the implementation of CSV. Snowball sampling was used to select 17 informants. Data collection methods included in-depth interviews and focus group discussions (FGDs) to ensure data triangulation. The CSR programs were effectively transformed into CSV by creating economic, social, and ecological value in partnerships between farmers and companies. The success of these partnerships hinged on establishing strong relationships through CSR initiatives. Community programs were developed to enhance farmers' capacities, integrating them as suppliers within the company's business chain. This study provides novel insights into the transition from CSR to CSV, demonstrating how companies can initiate CSR as a foundation for creating shared value and evolving into sustainable partnerships. The study highlights the interdependent relationships between farmers and companies, which generate significant social, economic, and ecological benefits. These partnerships facilitate farmers' access to markets and business capital, while companies benefit from a continuous supply of high-quality raw materials and reduced production costs.